Incidence and risk factors for five-year recurrent disc herniation after primary single-level lumbar discectomy: analysis of 733 patients. (1st March 2023) - Geere, Jonathan H.; Swamy, Girish N.; Hunter, Paul R.; Geere, Jo-Anne L.; Lutchman, Lennel N.; Cook, Andrew J.; Rai, Amarjit S.
Abstract : Aims: To identify the incidence and risk factors for five-year same-site recurrent disc herniation (sRDH) after primary single-level lumbar discectomy. Secondary outcome was the incidence and risk factors for five-year sRDH reoperation. Methods: A retrospective study was conducted using prospectively collected data and patient-reported outcome measures, including the Oswestry Disability Index (ODI), between 2008 and 2019. Postoperative sRDH was identified from clinical notes and the centre's MRI database, with all imaging providers in the region checked for missing events. The Kaplan-Meier method was used to calculate five-year sRDH incidence. Cox proportional hazards model was used to identify independent variables predictive of sRDH, with any variable not significant at the p < 0.1 level removed. Hazard ratios (HRs) were calculated with 95% confidence intervals (CIs). Results: Complete baseline data capture was available for 733 of 754 (97.2%) consecutive patients. Median follow-up time for censored patients was 2.2 years (interquartile range (IQR) 1.0 to 5.0). sRDH occurred in 63 patients at a median 0.8 years (IQR 0.5 to 1.7) after surgery. The five-year Kaplan-Meier estimate for sRDH was 12.1% (95% CI 9.5 to 15.4), sRDH reoperation was 7.5% (95% CI 5.5 to 10.2), and any-procedure reoperation was 14.1% (95% CI 11.1 to 17.5). Current smoker (HR 2.12 (95% CI 1.26 to 3.56)) and higher preoperative ODI (HR 1.02 (95% CI 1.00 to 1.03)) were independent risk factors associated with sRDH. Current smoker (HR 2.15 (95% CI 1.12 to 4.09)) was an independent risk factor for sRDH reoperation. Conclusion: This is one of the largest series to date which has identified current smoker and higher preoperative disability as independent risk factors for sRDH. Current smoker was an independent risk factor for sRDH reoperation. These findings are important for spinal surgeons and rehabilitation specialists in risk assessment, consenting patients, and perioperative management. Cite this article: Bone Joint J  2023;105-B(3):315–322.